Identification of a Vitis vinifera endo‐β‐1, 3‐glucanase with antimicrobial activity against Plasmopara viticola. (24th July 2016) - Mestre, Pere; Arista, Gautier; Piron, Marie‐Christine; Rustenholz, Camille; Ritzenthaler, Christophe; Merdinoglu, Didier; Chich, Jean‐François
Summary: Inducible plant defences against pathogens are stimulated by infections and comprise several classes of pathogenesis‐related (PR) proteins. Endo‐β‐1, 3‐glucanases (EGases) belong to the PR‐2 class and their expression is induced by many pathogenic fungi and oomycetes, suggesting that EGases play a role in the hydrolysis of pathogen cell walls. However, reports of a direct effect of EGases on cell walls of plant pathogens are scarce. Here, we characterized three EGases from Vitis vinifera whose expression is induced during infection by Plasmopara viticola, the causal agent of downy mildew. Recombinant proteins were expressed in Escherichia coli . The enzymatic characteristics of these three enzymes were measured in vitro and in planta . A functional assay performed in vitro on germinated P. viticola spores revealed a strong anti‐ P. viticola activity for EGase3, which strikingly was that with the lowest in vitro catalytic efficiency. To our knowledge, this work shows, for the first time, the direct effect against downy mildew of EGases of the PR‐2 family from Vitis .